2018
DOI: 10.1159/000486105
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Macular Degeneration with Sildenafil: Results of a Two-Year Trial

Abstract: Objective: To evaluate PDE5/6 inhibition with sildenafil to reduce choroidal ischemia and treat age-related macular degeneration. Methods: Sildenafil was prescribed to treat participants with macular degenerations or macular dystrophies measured by spectral-domain optical coherence tomography, color fundus photography, enhanced depth imaging, and best-corrected visual acuity. Results: No change in calcified drusen was noted. Vitelliform-type soft drusen were not substantially changed. A participant with Best v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
0
23
0
2
Order By: Relevance
“…Rho kinase inhibitors also have a potential therapeutic benefit in neovascular AMD [37]. Phosphodiesterase (PDE) inhibitors, including Viagra (sildenafil; Pfizer [38]), Levitra (vardenafil; Bayer), and Cialis (tadalafil; Eli Lilly), continue to raise interest among eye specialists for the hypoperfusion-related ocular pathologic disease treatment, including diabetic retinopathy and AMD [39]. G protein alpha was released by the activation of GPCRs, which provided a strategy for AMD treatment from a system pharmacology aspect [18].…”
Section: Discussionmentioning
confidence: 99%
“…Rho kinase inhibitors also have a potential therapeutic benefit in neovascular AMD [37]. Phosphodiesterase (PDE) inhibitors, including Viagra (sildenafil; Pfizer [38]), Levitra (vardenafil; Bayer), and Cialis (tadalafil; Eli Lilly), continue to raise interest among eye specialists for the hypoperfusion-related ocular pathologic disease treatment, including diabetic retinopathy and AMD [39]. G protein alpha was released by the activation of GPCRs, which provided a strategy for AMD treatment from a system pharmacology aspect [18].…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is that select patients with macular disease including CSCR may benefit from increased choroidal blood flow afforded by sildenafil. 14 , 15 , 16 We anticipate that sildenafil, administered with attention to “challenge” and “dechallenge” settings - that is, continued treatment beyond the initial resolution of serous fluid - should produce clinical improvement for these patients. The use of spironolactone – and eplerenone to a lesser extent - most closely parallels the present treatment but has shown slower treatment response and greater side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic treatment using a PDE5 and PDE6 inhibitor (sildenafil) is suggested as a means of increasing choroidal perfusion. Based on the hypothesis of increasing choroidal perfusion as a means of elevating NO (a messenger molecule) transfer across Bruch's membrane by PDE5 as well as the increase in photoreceptor regeneration caused by a decrease in Warburg glycolysis by PDE6, some studies treated a series of patients with AMD with systemic sildenafil [20].…”
Section: Amdmentioning
confidence: 99%
“…Coleman et al [20] conducted a 2-year trial to evaluate the effect of sildenafil measured by spectral-domain OCT, color fundus photography, EDI, and best-corrected visual acuity. The group concluded that sildenafil is a safe treatment for AMD or vitelliform macular degeneration and suggested that a thickened Bruch's membrane reduced the beneficial effect of the perfusion increase, but all eyes appeared to benefit from PDE6.…”
Section: Amdmentioning
confidence: 99%